Ethiopia Scaling Week - Ewell, Hanna; Byandaga, Livingstone; Seyoum, Yodit Y; Makonnen, Brook T.; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The AICCRA Ethiopia Scaling Week workshop, held at the Liesak Resort in Bishoftu, Ethiopia, 2- 4th April 2025, focused on advancing the responsible and inclusive scaling of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) solutions to enhance resilience among smallholder farmers in Ethiopia. It brought together 30 people (4 of whom were women) from various organizations, including the Ministry of Agriculture, the Ethiopian Institute for Agricultural Research, LERSHA, ILRI and ICARDA. The objective of the workshop was to engage in capacity sharing on the theory and practice of scaling, as well as to support the Ethiopia cluster in understanding and operationalizing the scaling framework of the AICCRA project by assessing CIS and CSA bundles and developing corresponding preliminary scaling pathways. Regarding methodological approaches, presentations were used to explain principles, with small groups' work and plenary discussions in a participative atmosphere. Based on the concepts and principles shared, participants reflected on their visions, the barriers they face, and accelerators or enabling factors to overcome them, and established roadmaps for four climate solutions: a community-based breeding program for small ruminants, a digital platform for feed and forage, site-specific fertilizer recommendations, and climate-informed agro-advisories.